Government Regulation of Foreign Economic Activity in Russia: Legal and Economic Aspects - Radzhabova, Z.K.; Radzhabov, O.R.; Osmanov, M.M.; Aygumov, T.G.; Emirova, G.A.; Khidirova, S.Z. (International Journal of Criminology and Sociology, 2021)
The paper assesses the fact that in the current conditions of globalization, any national economy is becoming more open, and therefore the state should take into account in its trade and economic policy the consistent relationship between the processes occurring within the economy and in the sphere of foreign economic relations. The state also acts as the organizer of the system of servicing foreign economic relations and achieving internal economic equilibrium, and finances this activity from budgetary funds. This system is branched in its nature, covering such areas of activity as the provision of information and consulting services, and organization of advertising and exhibition work; it also helps to increase the efficiency of foreign economic activity, introducing new participants to it. The authors conclude that in order to maintain domestic economic balance, the state should strengthen its influence on imports in order to maintain domestic producers and without depriving them of competition from foreign goods at the same time.